Morality and masculinity in the Carolingian empire - Stone, Rachel (Cambridge studies in medieval life and thought, 2012)
"What did it mean to be a Frankish nobleman in an age of reform? How could Carolingian lay nobles maintain their masculinity and their social position, while adhering to new and stricter moral demands by reformers concerning behaviour in war, sexual conduct and the correct use of power? This book explores the complex interaction between Christian moral ideals and social realities, and between religious reformers and the lay political elite they addressed. It uses the numerous texts addressed to a lay audience (including lay mirrors, secular poetry, political polemic, historical writings and legislation) to examine how Biblical and patristic moral ideas were reshaped to become compatible with the realities of noble life in the Carolingian empire. This innovative analysis of Carolingian moral norms demonstrates how gender interacted with political and religious thought to create a distinctive Frankish elite culture, presenting a new picture of early medieval masculinity"--